The Influence of Leadership Style, Work Discipline and Organisational Commitment on the Performance of Members of the East OKU Police Intel-ligence Unit - Andy Bintoro; Yunita Sari; Munajat (Law and Economics, 2026)
When it comes to furthering efforts to accomplish the goals of the Police Institution's creation and existence, human resources are the most crucial component. Issues related to the organisational commitment of members of the East OKU Police Intelligence Unit. The purpose of this study is to examine how personnel of the East OKU Police Intelligence Unit perform in relation to organizational commitment, work discipline, and leadership style.  The census method is the sampling strategy employed in the quantitative descriptive analysis research approach.  Multiple linear regression analysis is used in data processing and analysis.  The findings demonstrate that work discipline and leadership style have a major impact on OKU Timur Police Intelligence Unit members' performance.  In the meantime, OKU Timur Police Intelligence Unit members' performance is not significantly impacted by organizational dedication.